Development of the Career Indecision Profile: Factor Structure, Reliability, and Validity. (February 2013) - Hacker, Jason; Carr, Andrea; Abrams, Matthew; Brown, Steven D.
Prior research using a 167-item measure of career indecision (Career Indecision Profile-167 [CIP-167]) has suggested that career choice difficulties may be associated with four major sources of career indecision: neuroticism/negative affectivity, choice/commitment anxiety, lack of readiness, and interpersonal conflicts. The purpose of this study was to develop a shorter and more efficient measure of these four major sources of indecision for future use in research and counseling. The development of the measure (CIP-65) is described and the results of a confirmatory factor analytic study of its structure are presented along with initial reliability and validity data. We conclude by discussing implications for future research on the CIP-65 and its potential use in counseling individuals with choice-making difficulties.